Stem Cell Based Drug Delivery for Protection of Auditory Neurons in a Guinea Pig Model of Cochlear Implantation - Scheper, Verena; Hoffmann, Andrea; Gepp, Michael M.; Schulz, André; Hamm, Anika; Pannier, Christoph; Hubka, Peter; Lenarz, Thomas; Schwieger, Jana (Frontiers in Cellular Neuroscience, 2019)
Background: The success of a cochlear implant (CI), which is the standard therapy for patients suffering from severe to profound sensorineural hearing loss, depends on the number and excitability of spiral ganglion neurons (SGNs). Brain-derived neurotrophic factor (BDNF) has a protective effect on SGNs but should be applied chronically to guarantee their lifelong survival. Long-term administration of BDNF could be achieved using genetically modified mesenchymal stem cells (MSCs), but these cells should be protected – by ultra-high viscous (UHV-) alginate (‘alginate-MSCs’) – from the recipient immune system and from uncontrolled migration. Methods: Brain-derived neurotrophic factor-producing MSCs were encapsulated in UHV-alginate. Four experimental groups were investigated using guinea pigs as an animal model. Three of them were systemically deafened and (unilaterally) received one of the following: (I) a CI; (II) an alginate-MSC-coated CI; (III) an injection of alginate-embedded MSCs into the scala tympani followed by CI insertion and alginate polymerization. Group IV was normal hearing, with CI insertion in both ears and a unilateral injection of alginate-MSCs. Using acoustically evoked auditory brainstem response measurements, hearing thresholds were determined before implantation and before sacrificing the animals. Electrode impedance was measured weekly. Four weeks after implantation, the animals were sacrificed and the SGN density and degree of fibrosis were evaluated. Results: The MSCs survived being implanted for 4 weeks in vivo. Neither the alginate-MSC injection nor the coating affected electrode impedance or fibrosis. CI insertion with and without previous alginate injection in normal-hearing animals resulted in increased hearing thresholds within the high-frequency range. Low-frequency hearing loss was additionally observed in the alginate-injected and implanted cochleae, but not in those treated only with a CI. In deafened animals, the alginate-MSC coating of the CI significantly prevented SGN from degeneration, but the injection of alginate-MSCs did not. Conclusion: Brain-derived neurotrophic factor-producing MSCs encapsulated in UHV-alginate prevent SGNs from degeneration in the form of coating on the CI surface, but not in the form of an injection. No increase in fibrosis or impedance was detected. Further research and development aimed at verifying long-term mechanical and biological properties of coated electrodes in vitro and in vivo, in combination with chronic electrical stimulation, is needed before the current concept can be tested in clinical trials.